1996
DOI: 10.1002/pssa.2211570234
|View full text |Cite
|
Sign up to set email alerts
|

Na0.5Bi0.5TiO3–K0.5Bi0.5TiO3 (NBT-KBT) system: A structural and electrical study

Abstract: The study of the Na0.5Bi0.5TiO3–K0.5Bio0.5TiO3 (NBT‐KBT) system was carried out using X‐ray diffraction and dielectric measurements. The limits of rhombohedral and orthorhombic solid solutions were determined, as well as the evolution of their lattice parameters as a function of composition and temperature. Dielectric permittivity measurements in a wide frequency range between 20 and 800°C showed that all materials are ferroelectric at room temperature and exhibit a diffuse, probably second‐order phase transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(140 citation statements)
references
References 7 publications
3
135
2
Order By: Relevance
“…Bismuth sodium titanate (Bi 0.5 Na 0.5 )TiO 3 (BNT) has been recognized as one of the most promising candidates for the lead-free piezoelectric material [5,[10][11][12][13]. To clarify the origin of its ferroelectricity, the crystal structure has been intensively analyzed in detail [14][15][16][17][18][19][20][21][22]. The averaged structure of BNT has been reported to be a rhombohedral structure in space group R3c.…”
Section: Open Accessmentioning
confidence: 99%
“…Bismuth sodium titanate (Bi 0.5 Na 0.5 )TiO 3 (BNT) has been recognized as one of the most promising candidates for the lead-free piezoelectric material [5,[10][11][12][13]. To clarify the origin of its ferroelectricity, the crystal structure has been intensively analyzed in detail [14][15][16][17][18][19][20][21][22]. The averaged structure of BNT has been reported to be a rhombohedral structure in space group R3c.…”
Section: Open Accessmentioning
confidence: 99%
“…The solid solution of bismuth sodium titanate, (Bi 1/2 Na 1/2 )TiO 3 (BNT), and bismuth potassium titanate, (Bi 1/2 K 1/2 )TiO 3 (BKT), was synthesized by Elkechai et al in 1996 [56] and an increase in piezoelectric properties was observed in this system close to the rhombohedral to tetragonal morphotropic phase boundary, shown in figure 5. The existence of an MPB between (Bi 1/2 Na 1/2 )TiO 3 and (Bi 1/2 K 1/2 )TiO 3 in the compositional range 16-20 mol% (Bi 1/2 K 1/2 )TiO 3 was later substantiated by Sasaki et al [57] based on structural studies indicating coexistence of rhombohedral and tetragonal phases as well as the corresponding compositionally dependant peaks in the dielectric, piezoelectric and electromechanical coefficients.…”
Section: Bismuth Sodium Titanate-bismuth Potassium Titanate Solid Solmentioning
confidence: 99%
“…The replacement of Na þ in NBT with K þ leads to an increase in the piezoelectric response of the material 21,22 and a decrease in T d from $170 C to $100 C. 10,23,24 The composition and temperature-based structural changes are not well known because of the small distortions involved and reports of a wide two-phase region as a function of composition. 25 However, various electrical properties, including the piezoelectric coefficient d 33 , were found to be maximised at the composition (Na 0. 8 …”
Section: Introductionmentioning
confidence: 99%